IMPLEMENTASI PERDA KABUPATEN SEMARANG NOMOR 7 TAHUN 2016 TENTANG PENYELENGGARAAN ADMINISTRASI KEPENDUDUKAN : STUDI PENCATATAN KELAHIRAN - Wiwid Fitriani; Ida Hayu Dwimawanti; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The implementation of the birth registration policy as stipulated in the Regional Regulation of Semarang Regency Number 7 of 2016 has not gone well, as indicated by the ownership of birth certificates by only 53%. Even though a birth certificate is an important document related to the rights of citizens. This study aims to analyze the implementation of the Regional Regulation of Semarang Regency Number 7 of 2016 along with its supporting and inhibiting factors. The research method used is descriptive qualitative. The results of the study show that in its implementation, in terms of the deadline for reporting births, there are still residents who are late in reporting their birth events. Meanwhile, in terms of birth registration requirements, it is in accordance with applicable regional regulations. However, there are still people who are incomplete or do not comply with the provisions in attaching the requirements so that the application cannot be processed. Furthermore, in terms of the time frame for issuance of birth certificates, there are still delays in issuance caused by several factors. Then, the supporting factors for implementation are good communication between employees, adequate quality of human resources, availability of SOPs, clear authority, adequate budget, good disposition and commitment from executors, and a clear work structure. The inhibiting factors for implementation are delays in response from implementers, people who do not fully understand the policy, limited quantity of human resources, inadequate facilities, and limited access to data.